Method for determining the list of provincial science and technology tasks - Lessons from Ninh Thuan province - Tran Anh Tuan,; Ngo Van Duong,; Truong Thu Hang,; Le Tien Dung,; Vo Quang Lam, (Journal SCIENCE AND TECHNOLOGY POLICIES AND MANAGEMENT, 2024)
Ninh Thuan is a province located in the Southern Central Coastal region, with a favorable geographical location and many advantages for marine economic development. However, up to now, the socio-economic development process has not been commensurate with its inherent potential. The Resolution of the 14th Provincial Party Congress has set the goal that by 2025, the province will reach a well-developed level within the region and across the country. To achieve that goal, developing science and technology is one of the important solutions, among which applying new methods to determine the list of science and technology tasks to support socio-economic development and create a solid foundation for implementing long-term scientific and technological development in phases to proactively determine and utilize ideas and resources of the province and central government and socialize the implementation is an extremely necessary issue. Based on the previous period's research, the author proposes some policy suggestions for determining the list of S&T tasks of Ninh Thuan province in the period 2022-2025. Code: 23120501